Battling the social stigma of mental illnesses in Pakistan; what needs to be done? - Mansoor, Noman; Warsi, Aimen (Journal of the Pakistan Medical Association, 2023)
Dear madam, Awareness of mental disorders in adolescents is becoming increasingly important in global health and safety concerns, where anxiety disorders play an important role. Mental illnesses, also known as mental health disorders, refer to various mental health conditions that affect mood, thoughts, and behaviour. Examples of mental illnesses include depression, anxiety disorders, schizophrenia, eating disorders, and addictive behaviours [1]. Early diagnosis is the key to proper management of these conditions. Over 20 million Pakistanis (10% of the country's population) suffer from mental illness [2]. However, the disorders are not investigated due to the reluctance of patients to visit doctors and psychiatrists, which is attached to the social stigma and cultural barriers to mental health in Pakistan, thereby delaying the diagnosis. Like other South Asian societies where mental illnesses are thought to be linked to supernatural and religious phenomena [3], Pakistan’s predominantly conservative and orthodox communities are also dominated by similar beliefs. . A person with emotional symptoms is seen as a sign of weak faith. In traditional societies, mental illnesses are sometimes viewed as a result of social or moral transgression and is thought of as divine punishment, demonic possession, or witchcraft [4] [3]. The mentally ill are also perceived as dangerous, crazy, and incapable of friendship. This belief might also cause more social distancing and contribute to stigmatizing attitudes and stereotyping. When living in a society with these perceptions, the mentally ill often face shame and social exclusion [5]. The social impact of this stigma affects patients and threatens the entire social status of their families [5]. The fact that one's beliefs, religion, and morality are separate from their health must be embedded in society. The best way to spread this idea is through social media, mass media and awareness campaigns. Radio and television should popularize this idea and also educate people about the warning signs and symptoms of mental illnesses, such as lack of concentration to do something and feelings of invalid fear. Awareness campaigns should be targeted at rural areas where both education and medical care lack. Public presentations and discussions should be encouraged and promoted to increase awareness. Healthcare students as well as well as professionals should be enlightened of the importance of this field and encouraged to pursue their education in it. The social stigma associated with mental illnesses must be addressed and considered. ---Continue